2021
DOI: 10.21203/rs.3.rs-916555/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adoptive cell therapy targeting common p53 neoantigens in human solid cancers

Abstract: Adoptive cell therapy (ACT) targeting neoantigens can achieve durable clinical responses in patients with cancer. Most neoantigens arise from rare mutations, requiring highly individualized treatments. To broaden the applicability of ACT targeting neoantigens, we focused on TP53 mutations commonly shared across different cancer types. Here, we describe a library of T cell receptors (TCRs) that can target TP53 mutations shared among 7.3% of patients with solid cancers. These TCRs recognized tumor cells in a TP5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[4][5][6] Additionally, ex vivo expansion of TILs often results in further reduction and differentiation of TILs specific for neoantigens. 7 The low frequencies and/or differentiated phenotype of TILs can contribute to ineffective ACT. Methods We developed a protocol to selectively expand neoantigen-specific TILs by in vitro stimulation of target neoantigens, termed NeoExpand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Additionally, ex vivo expansion of TILs often results in further reduction and differentiation of TILs specific for neoantigens. 7 The low frequencies and/or differentiated phenotype of TILs can contribute to ineffective ACT. Methods We developed a protocol to selectively expand neoantigen-specific TILs by in vitro stimulation of target neoantigens, termed NeoExpand.…”
mentioning
confidence: 99%
“…While conventional TIL screening identified 3 T-cell receptors (TCRs), [8][9][10] NeoExpand enabled identification of 7 TCRs including the 3 TCRs identified by conventional screening. In vivo, 4196 TIL expanded through REP was ineffective in treating established TYK-nu human ovarian cancer cells that naturally expressed p53 R175H , 7 while the 4196 NeoExpand TILs effectively regressed the tumor in NSG mice. Single cell transcriptome analysis demonstrated that NeoExpand led to expansion of central memory/stem-like populations among the mutant p53-reactive clones in the 4196 TILs, while REP led to the depletion of the central memory/stem-like population.…”
mentioning
confidence: 99%